VP113 Reframing "Disinvestment": Appropriateness And Real-Time Data Capture. (2017) - Ronquillo, Charlene; Roome, Chris; Stein, Ken
Abstract : INTRODUCTION: Disinvestment – stopping the use of health technologies with little or no clinical benefits – can reduce health system costs and change practice towards effective innovations. In England, efforts to support disinvestment have included the National Institute of Health and Care Excellence (NICE's) list of 900+ "Do Not Do (DND) technologies". However, recent studies show ongoing, varying rates of DND technology, suggesting limited influence. In response, we propose a shift in perspective and reframing of the concept of 'disinvestment' to focus on 'appropriateness'. METHODS: We have developed a two-pronged approach to 'appropriateness'. The first develops local clinician agreements on specific, appropriate indications for a technology. The "RAND/UCLA Appropriateness Method" is being extended in this stage. This knowledge management process enables incorporation of local knowledge and practice via consensus development amongst local experts alongside scientific evidence. The second, and more novel, element is to specify and routinely collect data on technology use associated with these agreed indications. Shifting from cross-sectional clinical audits to real-time monitoring will highlight variation from the agreed indications, which can inform reimbursement policy and decisions. Evaluating the feasibility and sustainability of this approach will provide important lessons for scaling up. RESULTS: For clinicians, the reframing from disinvestment to appropriateness has important implications. The approach recognizes that there are very few technologies with absolutely no benefit. Framing the management of technology diffusion in terms of appropriateness emphasises benefits and maximises value for public health. Furthermore, combining local agreements on indications with real-time data capture facilitates intelligent, flexible commissioning and informs real-life evaluation. CONCLUSIONS: Shifting the perspective from disinvestment to appropriateness overcomes negative associations of stopping healthcare technologies. Linking clinically driven decisions on technology indications with routine data capture on use can transform clinical audit and healthcare commissioning. The combination of these approaches is, we believe, a novel approach on which more reflection and research will be valuable.